A ferida colonial, os museus e as lutas no campo: insurgências e práticas decoloniais no memorial das ligas e lutas camponesas - Tolentino, Átila Bezerra (2024)
This research aims to understand the strategies used and the limits faced by community museums linked to peasant struggles in an attempt to break with the logic underlying coloniality, in order to configure structures of disobedience to this logic through the politicization of their identities and collective memories. The analysis is based on the actions of the social agents that make up the Memorial of Struggles and Peasant Leagues - MLLC, located in the traditional rural community of Barra de Antas, in Sapé/PB. Theoretically and methodologically, the analysis of the observed phenomenon is based on decolonial critical theories, combined with the fields of study of Sociomuseology and Rural Sociology, with a focus on social museology and literature that allows understanding the social movement of the Peasant Leagues in the context of the brazilian peasantry. The study is characterized as field research with a qualitative approach and from the perspective of a “public sociology”, as proposed by sociologists Fernando Perlatto and João Marcelo Maia (2012). In addition to the bibliographical survey and research into primary, archival and audiovisual documents, a field study was carried out, based on the work that the researcher had already been developing, in an engaged and involved way, together with the MLLC team. The research was also supported by narratives from oral sources, first and second hand, from peasants who work or worked at the memorial, local agents and residents of Barra de Antas and its surroundings. We start from the assumption that the concrete social space where the memorial is located is impacted by the processes of coloniality that maintain their matrices of power, refracted in the privileges historically granted to an agrarian elite, which perpetuates the great concentration of land in the country and is reflected in Barra de Antas. Such privileges are sustained by the exploitation of peasant workers and by the physical and symbolic violence to which they were and are subjected, constituting a “colonial wound” (Mignolo, 2007) structuring the Brazilian agrarian issue, which permeates the history of the formation of Brazil as a State- nation and is perpetuated by processes of coloniality. This wound is also reflected in the collective memories of subalternized rural people, filled with trauma, pain, silencing and attempts to erase or manipulate memories. It was also necessary to understand how these colonial wounds have been dealt with by these groups in the constitution of their collective memories and in the musealization of their cultural references and social struggles.